Manejo de normas de bioseguridad en tiempo COVID- 19 en los profesionales Odontólogos del Distrito 19D04 Pangui – Yantzaza - Sánchez Cuenca, Angie Anahí (2021)
Dentistry professionals are directly exposed to contracting an infection that may endanger the integrity of patients and the personnel with whom they work, due to the inadequate use of biosecurity standards. The situation we are going through is extremely alarming, since it is the spread of the "COVID-19" virus, which is a respiratory viral disease caused by SARS-COV2, which causes a deadly disease. The objective of this research is to evaluate the application of the management of biosecurity standards in times of COVID-19 of dentistry personnel in District 19D04 Pangui - Yantzaza. This study is observational and transversal. The sample is made up of 100% of the Dentist Professionals of the 19D04 district, validated surveys were used to determine the level of knowledge and identify the biosecurity standards they apply. The information obtained was analyzed through the SPSS program. According to the results obtained in the application of the survey, it was determined that dentists in the 19D04 district have an adequate level of knowledge and proper management of biosafety standards, although there are 8.6% of dentists in the 19D04 district who have incorrect use of biosafety standards, due to the decrease in resources of public entities, lack of availability of PPE, chemical disinfection solutions, and high-level sterilization equipment (autoclave). KEYWORDS: Occupational Safety and Health Standards, Biosafety, COVID-19